2020
DOI: 10.1039/d0fo02379e
|View full text |Cite
|
Sign up to set email alerts
|

Black garlic melanoidins prevent obesity, reduce serum LPS levels and modulate the gut microbiota composition in high-fat diet-induced obese C57BL/6J mice

Abstract: The objective of this study was to assess the potential anti-obesity effects of black garlic melanoidins (MLDs) and gut microbiota changes in an animal model, hypothesizing that oral administration of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“… 79 . On the other hand, short chain fatty acids (SCFAs) derived from gut microbiota are involved in the pathogenesis of NASH, SCFA‐producing bacteria, such as S24‐7 80 and Bacteroidaceae , 81 could play beneficial roles in stimulating the immune response and protecting the mucosal barrier in mice. Our results indicated that VVYP treatment could restore gut microbiota by strongly enhancing the abundance of secondary BA‐producing bacteria ( Coriobacteriacease and Desulfovibrionaceae ) and SCFA‐producing bacteria ( S24‐7 and Bacteroidia ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 79 . On the other hand, short chain fatty acids (SCFAs) derived from gut microbiota are involved in the pathogenesis of NASH, SCFA‐producing bacteria, such as S24‐7 80 and Bacteroidaceae , 81 could play beneficial roles in stimulating the immune response and protecting the mucosal barrier in mice. Our results indicated that VVYP treatment could restore gut microbiota by strongly enhancing the abundance of secondary BA‐producing bacteria ( Coriobacteriacease and Desulfovibrionaceae ) and SCFA‐producing bacteria ( S24‐7 and Bacteroidia ).…”
Section: Discussionmentioning
confidence: 99%
“…Coriobacteriaceae, certain species of which have been proved to be beneficial to host lipid metabolism, 78 were increased after butyrate treatment. 25 It is well known that another important factor contributing to changes in the liver expression of genes is the interplay between gut microbiota and bile acid (BA) metabolism, protective gut microbiota(Desulfovibrionaceae and Coriobacteriaceae) associates with increased specific secondary BAs, which likely inhibit lipogenic pathways and enhance bile flow in the liver.. 79 On the other hand, short chain fatty acids (SCFAs) derived from gut microbiota are involved in the pathogenesis of NASH, SCFA-producing bacteria, such as S24-7 80 and Bacteroidaceae, 81 Previous studies demonstrated that another crucial participator in the progression of NASH is the network of pro-inflammatory chemokines and cytokines. 82,83 Several inflammatory factors, such as TNF-α, IL-1β and IL-6, have been proved to enable steatosis and liver damage, thus promoting the occurrence and progression of NASH.…”
Section: Discussionmentioning
confidence: 99%
“…When the number of harmful intestinal microbes is increased, their metabolites will lead to changes in the intestinal structure and permeability. Increased permeability also increased the number of microbes, the endotoxin or lipopolysaccharide ( LPS ) ( Wu et al., 2020 ), and harmful metabolites entering the intestine, causing systemic immune response, inflammation, and changes in the function of other organs and tissues ( Luci et al., 2019 ). There is a certain relationship between intestinal physiology and microorganisms and fatty liver formation induced by sugar ( Li et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Glucose metabolism pathway disorder induces liver fatty degeneration and intestinal mucosal barrier dysfunction in metabolism-associated fatty liver disease ( MAFLD ) ( Gao et al., 2020 ; Wang et al., 2020 ). Wu et al. (2020) reported that gut microbiota modulation can improve glucose tolerance, induce the production of Short Chain Fatty Acids and inhibit the production of endotoxin LPS.…”
Section: Introductionmentioning
confidence: 99%
“…16 A variety of biological activities of melanoidin has been demonstrated, including antioxidant, antibacterial, anti-in ammatory, hypoglycemic, hypotensive, antitumor effects, prevention of obesity, lowering of serum lipopolysaccharide levels, and modulation of the composition of the gut microbiota. 16,17 Additionally, inhibition against oxidation and angiotensin I converting enzyme were enhanced in black garlic comparing to raw garlic. 15 Therefore, the heating and ageing process not only preserved the food but also enhanced their biological activities.…”
Section: Introductionmentioning
confidence: 99%